Bio-inspired green synthesis of zinc oxide nanoparticles using Abelmoschus esculentus mucilage and selective degradation of cationic dye pollutants. (April 2019) - Prasad, Anupama R.; Garvasis, Julia; Oruvil, Shamsheera Kunnekkat; Joseph, Abraham
Abstract: In this study, biogenic zinc oxide nanoparticles (ZnO NPs) were fabricated via a green synthetic strategy using Abelmoschus esculentus (okra) mucilage. The NPs were characterized by Fourier transform infrared spectroscopy, Fourier transform-Raman, X-ray photoelectron spectroscopy, ultraviolet-visible spectroscopy, X-ray diffraction (XRD), thermogravimetry, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, high resolution transmission electron microscopy, and zeta potential analyses. The XRD pattern confirmed the hexagonal wurtzite structure of ZnO. The morphology of the NPs was uneven where they comprised heterogeneous particles with uniform spheres that had an average size of 29 nm, and elongated and rod-like structures measuring 70 nm. We proposed a possible mechanism for the formation of Zn5 (OH)6 (CO3 )2 micro-flakes and ZnO. The photocatalytic activities of the synthesized ZnO NPs was tested during the degradation of organic dyes comprising methylene blue, rhodamine B, Congo red, and methyl orange in aqueous solutions. The ZnO NPs were capable of the selective photodegradation of the target cationic dyes, where 125 mg of the catalyst removed 100% of the methylene blue solution (32 mg/L) within 60 min and 100 mg was required for the complete removal of rhodamine B (9.5 mg/L) within 50 min. Liquid chromatography-mass spectrometry analysis was conducted to confirm the photodegradation results. Thus, we developed a facile, economic, and green method for the production of ZnO for use as a photocatalyst. Highlights: ZnO nanoparticles (NPs) synthesized using Abelmoschus esculentus mucilage. Physicochemical studies indicated the formation of hexagonal wurtzite ZnO. Average size of NPs was 29–70 nm with variable morphology. ZnO NPs highly selective photocatalyst for degradation of cationic dyes.